Estimation of Heavy Metals in Dust Fall Samples from Three Different Industrial Areas of Karachi: Heavy Metals in Dust Fall (Biological Sciences - PJSIR, 2010)
The study of accumulation of heavy metals, Fe, Cu, Mn, Zn, Pb and Cd, in the dust fall samples, collected from three selected industrial areas of Karachi, showed the level of heavy metals to decrease gradually from sites of high activity to those of low activity such as from roundabouts to main roads to side roads. Concentration of heavy metal showed a variation of the order Fe>Zn>Pb>Mn>Cu>Cd. Iron had the highest concentration in all the sampling areas in the range of 1.947 ± 0.00 to 30.039 ± 0.01 mg/g. Lower values were observed for Cd with respective ranges of 0.001 ± 0.00 to 0.009 ± 0.01 mg/g. The results suggested that heavy metal pollution in the dust fall samples of industrial areas may be due to automobile and industrial exhaust from different industrial   units.